The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5114/jcb.2011.21037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigations Pulsed dose rate brachytherapy as the boost in combination with external beam irradiation in base of tongue cancer. Long-term results from a uniform clinical series

Abstract: PurposeTo evaluate long time outcome with regard to local tumour control, side effects and quality of life of combined pulsed dose rate (PDR) boost and hyperfractionated accelerated external beam radiotherapy (EBRT) for primary base of tongue (BOT) cancers.Material and methodsBetween 1994 and 2007, the number of 83 patients were treated with primary T1-T4 BOT cancers. Seven patients (8%) were T1-2N0 (AJCC stage I-II) and 76 (92%) patients were T1-2N+ or T3-4N0-2 (AJCC stage III-IV). The mean estimated primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has also been postulated that pulsing every second or third hour would be equivalent [12]. Long term clinical outcome data with PDR 24 pulses per day and 12 pulses per day are now available [13][14][15][16]. In contrast, when moving from LDR to HDR the total treatment dose has to be reduced depending on the dose per fraction.…”
Section: General Aspects Of Treatment Planning: Dose and Fractionationmentioning
confidence: 99%
“…It has also been postulated that pulsing every second or third hour would be equivalent [12]. Long term clinical outcome data with PDR 24 pulses per day and 12 pulses per day are now available [13][14][15][16]. In contrast, when moving from LDR to HDR the total treatment dose has to be reduced depending on the dose per fraction.…”
Section: General Aspects Of Treatment Planning: Dose and Fractionationmentioning
confidence: 99%
“…Brachytherapy is increasingly accepted as an alternative treatment for inoperable head and neck malignant neoplasms. High-dose brachytherapy and iridium-192 ( 192 Ir) IBT were used for tongue squamous cell carcinoma [28][29][30]. To the best of our knowledge, no research on brachytherapy or 125 I was reported in ACC of the BOT.…”
Section: Discussionmentioning
confidence: 99%